Professional Scrum With Team Foundation Server 2010 - Resnick, Steve ; Bjork, Aaron and De la Maza, Michael (Indianapolis Wiley Publishing Inc., 2010)
Provides information on using Visual Studio Team Foundation Server to execute a Scrum project, covering such topics as software project management, the tracking and reporting functions of TFS, using Scrum artifacts, creating product backlog items, and running a release.
Include Appendix, Reference and Index
Keywords: Microsoft Visual studio -- Agile software development -- Scrum (Computer software development)